A generic model to determine crack spacing of short and randomly oriented polymeric fiber-reinforced strain-hardening cementitious composites (SHCC) - Li, Junxia (2022)
Crack spacing is an important property governing the tensile strain capacity of strain-hardening cementitious composites (SHCC). This paper presents a generic model to determine the crack spacing of short and randomly oriented polymeric fiber-reinforced SHCCs, which takes into account of the fiber/matrix interface chemical bond, the fiber/matrix interface slip-hardening behavior, and two-way fiber pullout. The validity of the proposed model is assessed by comparing the crack spacing calculated from the present model with that observed from the direct tensile test. Increased chemical bond leads to reduced crack spacing at small crack opening due to increased fiber pullout force during fiber debonding. At large crack opening, however, increased chemical bond can lead to increased crack spacing due to premature fiber rupture. Furthermore, increased slip-hardening coefficient results in reduced crack spacing due to increased fiber pullout force during fiber slippage. Variation of the slip-hardening coefficient leads to more significant change of the crack spacing than that of the chemical bond. The proposed generic model can be used to determine the crack spacing of SHCC, and also to guide the design of SHCC with targeted multiple cracking pattern.